2010
DOI: 10.1523/jneurosci.0776-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Transient Glutamatergic Population Migrating from the Pallial–Subpallial Boundary Contributes to Neocortical Development

Abstract: The generation of a precise number of neural cells and the determination of their laminar fate are tightly controlled processes during development of the cerebral cortex. Using genetic tracing in mice, we have identified a population of glutamatergic neurons generated by Dbx1-expressing progenitors at the pallial-subpallial boundary predominantly at embryonic day 12.5 (E12.5) and subsequent to Cajal-Retzius cells. We show that these neurons migrate tangentially to populate the cortical plate (CP) at all rostro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(137 citation statements)
references
References 66 publications
(96 reference statements)
10
126
0
Order By: Relevance
“…A transient population of developing brain homeobox 1 (Dbx1) excitatory neurons migrates from the ventral pallium through the cortical subventricular zone, stimulating proliferative activity at embryonic stages. Subsequently, these Dbx1-positive neurons invade all cortical layers from the early postnatal period, but then largely disappear by adulthood (6,23). We thus favor the alternative explanation that this result is due to convergence of expression levels for genes that underlie common functional repertoires between nidopallium and neocortical layer IV.…”
Section: Resultsmentioning
confidence: 68%
“…A transient population of developing brain homeobox 1 (Dbx1) excitatory neurons migrates from the ventral pallium through the cortical subventricular zone, stimulating proliferative activity at embryonic stages. Subsequently, these Dbx1-positive neurons invade all cortical layers from the early postnatal period, but then largely disappear by adulthood (6,23). We thus favor the alternative explanation that this result is due to convergence of expression levels for genes that underlie common functional repertoires between nidopallium and neocortical layer IV.…”
Section: Resultsmentioning
confidence: 68%
“…Although early studies described tangential migration of presumed excitatory neurons in the embryonic cortex, they may have actually been describing tangentially migrating inhibitory neurons, which were discovered later (17). Interestingly, at least some rare (18), although usually transient (19,20), populations of excitatory cortical neurons migrate tangentially in the developing brain. Tangential migration of neural precursors in the developing hippocampus has previously only been observed in early postnatal developmental stages, during which the hippocampus is still immature and marked by ongoing growth and development (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dbx1-expressing cells located in the septum and the VP give rise to two different populations of Cajal-Retzius cells that populate the surface of the cortex (Bielle et al, 2005). The VP also seems to give rise to a transient population of glutamatergic cells that migrate tangentially to the neocortex (Teissier et al, 2010(Teissier et al, , 2011. In addition, it has been shown that the Dbx1-expressing progenitor cells located in the POA give rise to a unique population of GABAergic interneurons that populate the amygdala (Hirata et al, 2009).…”
Section: A Population Of Cortical Gabaergic Interneurons Derives Frommentioning
confidence: 99%
“…A small population of Dbx1-derived cortical GABAergic interneurons has also been recently identified (Teissier et al, 2010), but the origin and properties of these cells remain uncharacterized. To study this population of neurons, we crossed Dbx1 Cre mice with the reporter strain ROSA26 YFP (Srinivas et al, 2001) and analyzed the distribution of YFP-expressing cells in P30 mice.…”
Section: A Population Of Cortical Gabaergic Interneurons Derives Frommentioning
confidence: 99%
See 1 more Smart Citation